Implementasi Konsep “Smart” pada Interior Co-working Space “Semarang Digital Kreatif” di Semarang - Sia, Elvina Christina; Ronald Hasudungan Irianto Sitindjak; Stephanie Melinda Frans (Intra, 2019)
With the developing movement of the creative economy in Indonesia, the government of Semarang city government has finally cooperated in providing a free co-working space facility which is to provide the digital and non-digital communities in Semarang. Acknowledging the role importance of the “Semarang Digital Kreatif” facility to further improve creative economic activities in Semarang city, this reason is what ultimately became the base for the emergence of this design. The method used consists of 9 stages which are (1) understand, (2) observe, (3) point of view, (4) ideate, (5) prototype, (6) test, (7) story telling, (8) pilot , and (9) business model. The concept appointed in this design is “Representation of the Future”. The selected concept is inspired by the SDK facility itself which emphasizes on a digital basis, This design is expected to provide solutions which can accommodate a co-working space facility which can continue to develop further along with technological developments. The main facility design includes a co-working room which are divided into shared and private areas, which then also includes a meeting room, a lobby, and are also supported or equipped with facilities such as a pantry, an entertainment room, a lounge, toilets and prayer rooms.